Analysis of an antioxidative defence system of hydrogen peroxide-treated pancreatic islet-derived 1.1B4 cells and siRNA targeting NR4A3-treated cells by microarray - Motoko Nakayama; Etsuko Ueta; Mitsuru Yoshida; Yuri Shimizu; Atsuko Tokuda; Yasuko Sone; Yuri Nomi; Y. Otsuka (Taylor & Francis Group, 2023)
ABSTRACTPancreatic islet β-cells weaken under oxidative stress. In this study, human pancreatic islet-derived 1.1B4 cells were exposed to H2O2 and analysed using a human microarray, which revealed that heme oxygenase 1 (HMOX1), glutamate-cysteine ligase, early growth response 1, nuclear receptor subfamily 4 group A member 3 (NR4A3) and jun B proto-oncogene were upregulated, whereas superoxide dismutase 1 and catalase were not. Expression of NR4A3 rapidly increased after H2O2 addition, and the 1.1B4 cells treated with siRNA targeting NR4A3 became sensitive to H2O2; further, HMOX1 expression was strongly inhibited, suggesting that NR4A3 is an oxidative stress-responsive transcription factor that functions through HMOX1 expression in pancreatic islet β-cells. Expression of cyclin E1 and cyclin-dependent kinase 1 was also inhibited by siRNAs targeting NR4A3.